Targeted resequencing of FECH locus reveals that a novel deep intronic pathogenic variant and eQTLs may cause erythropoietic protoporphyria (EPP) through a methylation-dependent mechanism - Chiara, Matteo; Primon, Ilaria; Tarantini, Letizia; Agnelli, Luca; Brancaleoni, Valentina; Granata, Francesca; Bollati, Valentina; Di Pierro, Elena (Genetics in medicine, 2020)
Purpose Existing data do not explain the reason why some individuals homozygous for the hypomorphic FECH allele develop erythropoietic protoporphyria (EPP) while the majority are completely asymptomatic. This study aims to identify novel possible genetic variants contributing to this variable phenotype. Methods High-throughput resequencing of the FECH gene, qualitative analysis of RNA, and quantitative DNA methylation examination were performed on a cohort of 72 subjects. Results A novel deep intronic variant was found in four homozygous carriers developing a clinically overt disease. We demonstrate that this genetic variant leads to the insertion of a pseudo-exon containing a stop codon in the mature FECH transcript by the abolition of an exonic splicing silencer site and the concurrent institution of a new methylated CpG dinucleotide. Moreover, we show that the hypomorphic FECH allele is linked to a single haplotype of about 20 kb in size that encompasses three noncoding variants that were previously associated with expression quantitative trait loci (eQTLs). Conclusion This study confirms that intronic variants could explain the variability in the clinical manifestations of EPP. Moreover, it supports the hypothesis that the control of the FECH gene expression can be mediated through a methylation-dependent modulation of the precursor messenger RNA (pre-mRNA) splicing pattern.